The builds and functional relations Between the peopolitics and strategy (Journal of the College of Education for Women, 2019)
The geopolities considering as build from the basies builds of the politiesgeography, participating in appointing the military geography, and submit to itgeo-polities purveyed, playing important role to appointing the builds relationsbetween the high strategy and the military strategy, while the foreign polities ofthe state, which considering as a tool for the state outside it environment andborders playing the role of the performance and the functional works to thepeaceful or hostile reaction according to the geopolities purveyed whichparticipating in amassing the recourse for the economical, political, social,military and technology strategies and activating it to achieving the state interestsand objects.